Unveiling The Impact of Covid-19 And The Policy Implications On Indonesian Small Businesses: Where Do They Hurt The Most? - Wahyuni, Sri; Ikasari, Novita (UI Scholars Hub, 2022)
The catastrophic impact of COVID-19 Pandemic on micro, small and medium enterprises (MSMEs) is well-presented across countries featured on a helicopter view. However, studies on business activities as proxies to business functions that are exclusively affected by the pandemic are scarcely found, which in turn might cause ineffective recovery policy. Using Indonesia as a case in point, this study aims at codifying the particular business activities to proxy the functions that have been impacted across the sectors and business owners’ perception on the government’s policy. The study uses indicators for three business functions that are qualitatively constructed from previous studies to ensure their robustness. Data from the 220 respondents across Indonesia are collected using a non-probability sampling technique and the questionnaire is distributed online. The results are presented in descriptive statistics along with Kruskal-Wallist test to detect any difference across industries and duration of business. The study finds that production is the most severely impacted on creative sectors, whilst human resources issues are rampant for manufacturing and financial issues remain the center of the conundrum for all sectors. Notwithstanding the fatalistic result of downfall in demand of goods and services, the second most impacted business activity is productivity due to the reduced working hour of employees. In terms of COVID-19 Pandemic policy, financing facilities and health protocol are equally impactful for small businesses. These findings provide unambiguous evidence on specific business activities that are impacted, that is beneficial for evidence-based policy making.